Extraction of volatile compounds from pandan leaves (pandanus amarylifollius roxb.) using Pressurised Liquid Extraction (PLE) / Fatimahtun Zahra Mohamed Ridzuan - Mohamed Ridzuan, Fatimahtun Zahra (2012)
Pandan (Pandanus amarylifolius Roxb.) leaf is a source of natural flavouring and colouring widely used in South-east Asia. The major constituent of Pandanus amarylifolius has been reported 2-acetyl-1-pyrroline which is responsible for flavour. Usually pandan flavour available in the market is synthetic, so that this study is to introduce a natural pandan flavour based on the extraction. Commonly conventional method have disadvantages like long extraction time and thermally destructive process, so that the study to introduce Pressurised Liquid Extraction (PLE) as one of applicable method to extract pandan volatile oil. The objective of this research is to determine the flavour profile, quality and sensory acceptability of the extracted oil by using PLE, hydrodistillation and Soxhlet extraction. In this research, the method of drying, extraction, separation and analysis are used and the sample is separated from the solvent by using a rotary evaporator to get the essential oil. Almost 80% of water in pandan leaves can be removed by drying. Yields of PLE extracts were greater when compared to hydrodistillation and Soxhlet extraction.